Zakres funkcji opiekuńczo-zabezpieczającej rodziny - Kotlarska-Michalska, Anna (Wydział Prawa i Administracji UAM, 1985)
The present article contains the review of various means of handling the tutelar and securing functions of a family in the Polish sociological literature. The differences in handling of that function are resulting from ,a various understanding of function's essence. For some it means effects of acts, for others it is acts performed by a family or goals a family is aiming at. Various ranges (sets of: acts, actions, goals) .and names of the same function are consequence of the unequivocal understanding of function. The „tutelar and educational function" and „securing function" are the names in most frequent use. Irrespective of the function's name it is is often ascribed the following acts: tutelar, care, services, various forms of material benefits and acts of prevention and securing. Any of the presented definitions includes a distinct „set" of acts. The review of the frequently used denominations for the tutelar and securing functions prove that they can be handled in three ways: a) as an autonomous function, posessing the own range, b) the two-range function being a merger of two functions, e) non-autonomous function included in the range of several other functions. Complexity of the tutelar and securing functions and the methologieally desired necessity to differentiate it from the whole of family functions induced the authoress to present a descriptive-enurrerative definition containing explicitely all substantial acts actions and attitudes.
The scope of tutelar and securing functions of a family